Effect of Antihypertensive Treatment with Doxazosin on Insulin Sensitivity and Fibrinolytic Parameters - Zehetgruber, Manfred; Christ, Günter; Gabriel, Harald; Mundigler, Gerald; Beckmann, Renate; Binder, Bernd R.; Huber, Kurt (Thrombosis and Haemostasis, 1998)
The effects of the selective alpha-1-adrenoceptor antagonist doxazosin on metabolic and fibrinolytic parameters were studied in hypertensive patients with various degrees of fasting plasma insulin levels (Group A: 22.5 ± 3 μU/ml, Group B: 8.1 ± 1.5 μU/ml; p <0.01) to disclose a potential link between a doxazosin-induced alteration of insulin and/or lipid metabolism and possible changes of these parameters on the fibrinolytic system. Doxazosin treatment resulted in a dose-dependent reduction of basal insulin levels in group A to 16 ± 3 μU/ml; p <0.05. This finding was paralleled by a dose-dependent increase in t-PAmass concentration in the same patient group (basal t-PAmass from 9.7 ± 1 to 15.5 ± 2 ng/ml; p <0.05). As PAI-1 “active” as well as total antigen levels were not altered in parallel, the net effect on the endogenous fibrinolytic system is an increase of the fibrinolytic potential.